“Efecto de los bioestimulantes foliares a base de algas marinas, sobre el desarrollo y rendimiento del cultivo de maíz (Zea mays L.), en la zona de Pimocha”. - Icaza Olvera, José María (2019)
SUMMARY The present experimental work was carried out in the lands of Mr. Carlos Mujica Guerrero, located in the "San Isidro" enclosure, belonging to the Pimocha parish, Babahoyo Canton. The geographical coordinates are 110597.97 UTM south latitude and 277438.26 UTM west longitude and 8 msnm. The zone presents a humid tropical climate, with average annual temperature of 25.40 ° C, annual precipitation of 2 048.00, average evaporation of 1 132.90 mm, relative humidity 79% and 725.10 hours of annual heliophany. The soil is flat topography, clay loam texture and regular drainage. The INDIA S - 505 corn hybrid was used as seed material. The present experimental work had eight treatments and three repetitions, with the use of Stimplex (Ascophyllum nodosum), in doses of 0.75 and 1.0 L / ha. ; Kelpak (Ecklonia maximum), in doses of 0.75 and 1.0 L / ha; Basfoliar algae (Durvillea antarctica) in doses of 0.75 and 1.0 L / ha; a chemical control (Cytokin) in a dose of 1.0 L / ha and a control without application. The experimental design of Complete Blocks at Random was used with 8 treatments and 3 repetitions. To perform the evaluation of the means of the treatments, the Tukey test was used at 95% probability. For the execution of the trial, all the practices and agricultural work that the crop requires for its normal development were carried out, such as land preparation, sowing, weed control, phytosanitary control, fertilization, irrigation and harvesting. Based on the results obtained, it was determined that foliar biostimulants based on marine algae caused positive effects in the maize crop in the Pimocha area; the agronomic characteristics of plant height, height of cob insertion, diameter and length of ear, grains per ear, weight of 1000 grains and grain-peel ratio obtained better averages with the use of biostimulant Basfoliar algae (Durvillea antarctica) in doses of 1.0 L / ha applied at 20 and 40 days after sowing and the use of Basfoliar algae (Durvillea Antarctica) in a dose of 1.0 L / ha influenced the corn crop to obtain better yields with 6423.2 kg / ha and a net economic benefit of $ 227.3. Keywords: biostimulants, corn, yield.